Örter - Nilsson, Cristian (2005)
A tight economy and a keen competition force the Swedish agricultur to do a structural rationalization. The quantity of farmers is less but the units are growing. How to make money I think some kind of niche is necessary. In my examwork I have locked how to farm herbaceous plant and the marking of herb to feedstuff for horses. Today health food and alternative medicine are accepted to use and there is an increase in demand. The Swedish market for herbaceous plants to horses is small and the products are mostly imported. But there is a group of consumers who is willing to pay a higer price for Swedish cultivated herbs. The only way to find out which herbaceous plants I could cultivate is to make a test cultivate. I think that the market for herbaceous plants is growing. Some of the herbaceous plants are like weeds and can make a problem into other crops. It is important to be consistent from the beginning and prevent the herbaceous plants to shed their seed. But if you can handle this problem I think it is a good business to cultivate herbaceous plants.